2012
DOI: 10.1097/coc.0b013e318210f9b5
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Reducing Cancer Incidence and Mortality in African American and Arab American and Chaldean Communities in the Detroit Metropolitan Area

Abstract: The results of this study suggest that implementing CBPPs are feasible in underscreened ethnic minority populations. Further studies need to be performed to determine the absolute benefit of CBPPs compared with baseline levels of screening within these ethnic minority populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…The barriers to screening and treatment of cancer among Arab Americans included lack of knowledge ( 100 103 ), religious and cultural beliefs about sickness ( 100 , 104 ), fear and embarrassment ( 98 , 103 ), language ( 101 , 104 ), lack of culturally sensitive healthcare providers ( 100 ), lack of access to healthcare ( 105 ), and a need to maintain secrecy of sickness or disease ( 99 ). Community based participatory research was conducted among Arab Americans to address cancer education, prevention, and screening ( 106 ). This type of research was successful and found to increase cancer screening rates among an Arab American community in Detroit and can be used in future studies aiming to improve education and screening of other diseases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The barriers to screening and treatment of cancer among Arab Americans included lack of knowledge ( 100 103 ), religious and cultural beliefs about sickness ( 100 , 104 ), fear and embarrassment ( 98 , 103 ), language ( 101 , 104 ), lack of culturally sensitive healthcare providers ( 100 ), lack of access to healthcare ( 105 ), and a need to maintain secrecy of sickness or disease ( 99 ). Community based participatory research was conducted among Arab Americans to address cancer education, prevention, and screening ( 106 ). This type of research was successful and found to increase cancer screening rates among an Arab American community in Detroit and can be used in future studies aiming to improve education and screening of other diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have improved upon the past literature by providing estimates of depression and depression symptoms among larger groups of Arab Americans alongside the examination of the risk factors (and resiliency factors) associated with this improved mental health but very few studies report on interventions to reduce mental health outcomes. Studies of cancer among Arab Americans have also increased in number since the last review, with a number of studies identifying incidence of a variety of cancers in Arab Americans ( 106 110 ) and another set of studies identifying barriers to screening, care and treatment in this population ( 97 105 , 203 ). There have been more studies examining the risk of diabetes and cardiovascular disease in Arab Americans since 2009 ( 34 43 , 112 , 121 , 141 , 204 206 ), and more recent studies have examined successful targeted interventions to reduce risk factors for these diseases in ethnic enclaves ( 41 – 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Members of the CCOP were present to help inform participants about the clinical trials currently available at WBH as well as the individual and societal/community benefits provided by participating in clinical trials. The success of the MOP in improving screening rates was published recently, and MOP forums leading to a relative increase in screening rates of 38.6% and 28.7% for breast cancer and prostate cancer, respectively, compared with historic controls of screening within minority populations 15…”
Section: Methodsmentioning
confidence: 99%
“…Health forums in Michigan have been reported to be effective at increasing cancer screening estimates. For example, among Arab American men who attended a cancer forum, 28.9% obtained a PSA test (Vicini et al, 2012). Therefore, such educational forums may be useful in increasing screening estimates for other preventive behaviors, such as flu and pneumonia vaccines.…”
Section: Discussionmentioning
confidence: 99%